Diet and Exercise Patterns with Postprandial Blood Glucose Tests in Diabetes Mellitus Patients at Kaliwungu Health Center - Elvira P, Anastasya; Sukarmin, Sukarmin; Yulisetyaningrum, Yulisetyaningrum (Jurnal Keperawatan Profesional (KEPO), 2025)
Diabetes Mellitus is a chronic condition with an increasing prevalence worldwide, including in Indonesia. According to IDF data from 2021, the global prevalence of DM was 10.5%, and it is predicted to rise to 12,2% by 2045. Managing DM focuses significantly on controlling postprandial blood sugar levels, as it plays a crucial role in prevention efforts. This study investigated the relationship between dietary and exercise patterns and postprandial blood glucose levels in diabetes mellitus patients at the Kaliwungu Health Center. Using a correlational study design, the research targeted 164 registered DM patients, with 115 participants selected via purposive sampling. Data on diet and exercise were collected through questionnaires, while postprandial blood sugar levels were measured using an electric glucose test. The analysis utilized the Pearson correlation test or the Spearman rho test for non-normally distributed data. The results revealed a p-value of <0,001 (p-value < 0,05) significance level, confirming a significant relationship between diet and exercise patterns and postprandial glucose levels. Contingency coefficients of 0,588 and 0,532 demonstrated a moderately strong association between these variables.